Gobierno abierto y la administración pública en la Dirección Regional de Salud de Loreto 2024 - Noriega Noronha, Nancy Elizabeth (2025)
The objective of this research work was to determine how open government and public administration are related in the Regional Health Directorate of Loreto 2024. The study is basic, with a quantitative, correlational approach, and had a non-experimental and transversal design, in this study a causal non probabilistic sample was used. The sample was made up of 70 collaborators. In this study, the survey and questionnaire were used as instruments. The results showed that, of a total of 210 respondents in Open Government and Public Administration in the Regional Health Directorate of Loreto 2024, 6.7% responded that they totally disagree with open government in the Regional Directorat of Health of Loreto 2024, therefore, 13.3% commented that they agreed, in addition, 13.3% stated that they disagreed, on the other hand, 20.0% expressed that they neither agreed nor disagreed, while 46.7% affirm that they totally agree with open government in the Regional Health Directorate of Loreto 2024. Concluding that there is a direct relationship between open government and public administration. in the Regional Health Directorate of Loreto 2024, is based on the principles of transparency, participation, collaboration and innovation, which contributes to more efficient management focused on the well-being of the population.